2004
DOI: 10.1149/1.1768131
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Anode-Supported Tubular SOFCs with Zirconia-Based Electrolyte for Reduced Temperature Operation

Abstract: An anode-supported tubular solid oxide fuel cell ͑SOFC͒ with a thin electrolyte film for reduced temperature operation was fabricated by a wet cofire process. Instead of the traditional extrusion method, the anode substrate was formed by a tape-cast method. This allows design the substrate with some advantageous configurations that can improve the performance of SOFCs. Sc 2 O 3 and Y 2 O 3 -stabilized zirconia electrolyte films were fabricated on the substrate by a modified slurry dip-coating method and then c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Maximum power densities of LSGM-based tubes amounted to 482 mW/cm 2 at 800°C for 220 μm-thick electrolyte tubes. Anode-supported cells (ASC) were reported by Nguyen [3], Sarkar [4], Funahashi [5] and Suzuki [6]. Maximum power outputs reached up to 1017 mW/cm 2 at 550°C [6].…”
Section: Introductionmentioning
confidence: 99%
“…Maximum power densities of LSGM-based tubes amounted to 482 mW/cm 2 at 800°C for 220 μm-thick electrolyte tubes. Anode-supported cells (ASC) were reported by Nguyen [3], Sarkar [4], Funahashi [5] and Suzuki [6]. Maximum power outputs reached up to 1017 mW/cm 2 at 550°C [6].…”
Section: Introductionmentioning
confidence: 99%
“…A key technology of low operating temperature for SOFCs is developing cathode which is well operated at low temperature. The composition of La 0.6 Sr 0.4 Co 0.3 Fe 0.7 O 3-d (LSCF) is the most common used as the cathode materials of SOFCs due to high oxygen surface and tracer diffusion coefficients at high temperature at and above 700 C [3]. It is reported that the metal additives such as Ag, Pr, and Pd nanoparticles reinforced LSCFs show high catalytic activity such as oxygen adsorption, desorption, dissociation and diffusion because of the typical properties of metal nanoparticles [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that anode-supported SOFCs in which the anode comprises a very thin electrolyte film such as YSZ coated on a porous Ni-YSZ substrate make possible a high power density, a low operating temperature and a low manufacturing cost [5,6]. Consequently, many researchers have attempted to combine the favourable properties of the tubular SOFC configuration with the anode-supported design approach to realise highly efficient, low-temperature SOFC systems [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%